COASTAL AND MARINE ECOSYTEMS MANAGEMENT STRATEGY IN INDONESIA - Supriharyono . (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Its is well known that estuaries , mangroves, seagrasses beds, and coral reefs are productive ecosystems in the coastal marine areas. The production may goes up to 3.000 g C/m2/year. It is very high compared with the production in open seas that only 50 – 100 g C/m2/year. The coastal water ecosystems are also known as good habitat for spawning, nursering, and feeding several species of fish. Therefore, the secondary productivity is also high in these ecosystems. Anthropogenic activities in order to used the resources in coastal areas, however, are often dangerous to the life of those ecosystems. Considering to the anthropogenic activities, the Indonesian government have established several law and regulation for marine environmental protection. These included the establishment of 23 marine conserves areas which cover areas of about 2.800.000 Ha. These areas are expected will be expected will be expanded to 10.000.000 Ha by the end of 1995, and 30.000.000 Ha by the year of 2000.